Diagnostic and therapeutic strategies for vascular complications after renal transplantation: a single-center experience in 2,304 renal transplantations - Zhang, Jiangwei; Xue, Wujun; Tian, Puxun; Zheng, Jin; Ding, Chenguang; Li, Yang; Wang, Ying; Ding, Xiaoming (Frontiers in Transplantation, 2023)
Vascular complications after renal transplantation are one of the serious surgical complications, which can affect the transplantation outcome and even endanger life if not treated properly. We performed a retrospective analysis of the 2,304 renal transplantations procedures completed between the period of Jan., 2015 and Jan., 2022, which consisted of 1,658 male patients and 646 female patients. Among the above cases, there were 54 cases of vascular complications after renal transplantation, the incidence of vascular complications in our study was 2.34% (54/2,304), the most common vascular complication was transplanted renal artery stenosis (TRAS, n = 36), followed by external iliac artery dissection (n = 5), renal artery rupture (n = 4), renal vein thrombosis (n = 3), renal artery thrombosis (n = 2), renal artery dissection (n = 1), renal artery pseudoaneurysm (n = 1), and internal iliac artery pseudoaneurysm (n = 1), and renal artery kinking (n = 1). 40 patients were treated by percutaneous transluminal angioplasty (PTA), including 3 balloon catheter dilatation and 37 endovascular stentings, and 14 underwent open surgery. Eventually, 9 patients had graft nephrectomy, resulting in an overall treatment rate of 81.5%. Most vascular complications can be treated satisfactorily with PTA. However, the overall treatment of renal artery rupture, thrombosis, renal artery kinking, and other complications is poor, and the rate of transplanted renal loss is high.